The effect of vitamin D2 supplementation on muscle strength in early postmenopausal women: a randomized, double-blind, placebo-controlled trial. (3rd September 2018) - Suebthawinkul, C.; Panyakhamlerd, K.; Yotnuengnit, P.; Suwan, A.; Chaiyasit, N.; Taechakraichana, N.
Abstract: Background: Low serum 25-hydroxyvitamin D [25(OH)D] has been shown to be associated with low muscle mass and loss of muscle strength, resulting in increased disability and frailty in older men and women. Vitamin D deficiency is common in postmenopausal women. The primary objective of the present study was to evaluate the effects of vitamin D supplementation on muscle strength in early postmenopausal women. The effects of vitamin D2 supplementation on muscle mass and muscle cross-sectional area (CSA) were secondarily investigated. Methods : A 12-week, prospective, randomized, double-blind, placebo-controlled trial was conducted in early postmenopausal women (45–60 years old) with vitamin D deficiency (serum 25(OH)D < 20 ng/ml). A total of 88 subjects were randomized into group I: vitamin D2 supplement 40 000 IU/week ( n  = 44), or group II: placebo ( n  = 44). Serum 25(OH)D level, muscle strength, muscle mass and muscle CSA were assessed at baseline and 12 weeks after the supplementation. Results : After 12 weeks of supplementation, 70% of women in group I achieved a sufficient level of serum 25(OH)D (>30 ng/ml). There were significant differences in changes of serum 25(OH)D levels between the two groups ( p  < 0.05). Muscle strength and muscle CSA in group I increased significantly after 12 weeks ( p  = 0.015, 0.045, respectively). However, there were no significant differences in the mean changes of muscle strength, muscle mass and muscle CSA between the two groups ( p  = 0.16, 0.89, 0.84, respectively). Conclusion : In this study, we found no obvious effect of vitamin D supplementation on the changes in muscle strength, muscle mass and muscle CSA when compared to placebo. However, there were significant changes in muscle strength and muscle CSA from baseline in the vitamin D supplementation group.